Application of Wordwall Media to increase learning motivation in learning the History of Colonialism and Imperialism in class XI-6 SMA Negeri 5 Medan - Perangin-Angin, Elsima Br; Nasution, Abd Haris; Nasution, Sovianur (Jurnal Akuntansi Hukum dan Edukasi, 2024)
This research aims to increase student motivation in studying in class XI-6 students at SMA Negeri 5 Medan in studying the history of colonialism and imperialism through the use of the Wordwall web media. The classroom action research method was applied in three stages. The research results showed a significant increase in students' learning motivation after using Wordwall. In the second stage, student learning motivation reached 81%, an increase from 50% in the initial stage. These findings indicate that Wordwall has the potential to be an effective tool for increasing student interest and engagement in history learning.